PhysioSoft : an approach in applying computer technology in biofeedback procedures - Havelka, Mladen (Array, 2009)
Abstract: The paper presents description of original biofeedback computer program called PhysioSoft. It has been designed on the basis of the experience in development of biofeedback techniques of interdisciplinary team of experts of the Department of Health Psychology of the University of Applied Health Studies, Faculty of Electrical Engineering and Computing, University of Zagreb, and »Mens Sana«, Private Biofeedback Practice in Zagreb. The interest in the possibility of producing direct and voluntary effects on autonomic body functions has gradually proportionately increased with the dynamics of abandoning the Cartesian model of body-mind relationship. The psychosomatic approach and studies carried out in the 50-ies of the 20th century, together with the research about conditioned and operant learning, have proved close inter-dependence between the physical and mental, and also the possibility of training the individual to consciously act on his autonomic physiological functions. The new knowledge has resulted in the development of biofeedback techniques around the 70-ies of the previous century and has been the base of many studies indicating the significance of biofeedback techniques in clinical practice concerned with many symptoms of health disorders. The digitalization of biofeedback instruments and development of user friendly computer software enable the use of biofeedback at individual level as an efficient procedure of a patient’s active approach to self care of his own health. As the new user friendly computer software enables extensive accessibility of biofeedback instruments, the authors have designed the PhysioSoft computer program as a contribution to the development and broad use of biofeedback